Isolation of swarm sources using InSAR: the case of the February 2017 seismic swarm in western Anatolia (Turkey). Issue 3 (19th February 2019) - Svigkas, Nikos; Atzori, Simone; Kiratzi, Anastasia; Tolomei, Cristiano; Salvi, Stefano
SUMMARY: We study the surface deformation of a moderate size M 5+ earthquake swarm-type activity which burst at the tip of the Biga peninsula (western Turkey) in early 2017. No previous M 5+earthquakes have been recorded in the instrumental period on land, however, offshore normal faults, have ruptured to produce strong ( M > 6) earthquakes. We use the Interferometric Synthetic Aperture Radar (InSAR) technique and exploit a data set of Sentinel-1 and ALOS-2 images, to successfully detect the surface deformation caused by three M 5+ events of the sequence and constrain their source models, furtherly strengthened by seismic waveform analysis. The sequence occurred at shallow depths (<12 km) and is related with the activation of a normal fault. Our geodetic inversions constrained the rupture distribution of the main events and led us to conclude that they belong to a single fault plane, striking N110°E and dipping ∼40° to the SW, compatible with the regional tectonics. Furthermore, the InSAR analysis revealed that no aseismic transients occurred during the Biga swarm. InSAR applications in seismic swarms are limited mainly due to the low displacement signal they produce, which is not always easily detectable by radar satellites. Another obstacle is the time frequency of radar satellites acquisitions that often does not allow the temporal isolation of distinct seismic events. However, here we present a study that exploits InSAR data to isolate seismic sources of a swarm and proposes its use for the understanding of shallow seismic swarms in a systematic manner.